Investigation of surfaces effects on ice formation - Ong, Zile (2019)
Hydrophobicity has been a popular area of research, giving surfaces properties such as self-cleaning, water repellent and friction reduction. Another key area of study is the relationship between hydrophobic surfaces and anti-icing properties, which could be beneficial for applications where ice formation is avoided, such as on aircrafts and wind turbines. One of the common fabrication methods for producing hydrophobic surfaces is chemical etching, due to its low cost and high efficiency. In this study, 1100 Aluminium Alloy plates were chemically etched using Hydrochloric Acid (HCL) as the etchant, before being immersed in ethanolic stearic acid for passivation of the etched plates. Based on past studies, the hydrophobicity of the surface can be affected by the etching duration and the etchant concentration used. As such, there is an optimal combination of etching duration and etchant concentration that will produce the ideal hydrophobic surface. The test plate that was etched with 4M HCL for 6 minutes produced the most hydrophobic surface, with an average contact angle value of 155.02°. To determine the changes in icing properties of the test plates, an icing experiment was designed to measure the time it takes for ice formation to start on the etched surfaces. In general, the plates that were etched in 4M HCL showed faster ice formation rates as compared to the control plate and the plates etched in 3M HCL. It is found that there is a correlation between the contact angle values and the icing properties of the surface, where plates with higher contact angle values producing ice faster. In fact, the largest drop in ice formation timing was achieved by the test plate with the highest contact angle of 155.02°. It was also found that the amount of ice produced has a positive relationship with the first ice formation timing, and more ice was formed on the surfaces with higher contact angle values.